Genotype, environment, and management interactions on grain yield and nutrient uptake dynamics in winter wheat - De Oliveira Silva, Amanda (Kansas State University, 2019)
Understanding factors underpinning the variation in nitrogen (N) utilization efficiency (NUtE) [i.e., grain yield per unit of N uptake at maturity] is critical to direct future breeding and agronomic management strategies in wheat. However, no study has summarized changes in wheat NUtE across a wide range of environments. Further, the conservative behavior of producers to intensify management practices may have been contributing to the yield stagnation in the US southern Great Plains. Our goals were to: (i) perform a synthesis-analysis using published data to study NUtE in wheat, and (ii) conduct field studies to investigate the influence of genotype, environment, and management on grain yield and nutrient uptake. Results from our synthesis-analysis (n=529) showed a positive and curvilinear relationship between grain yield and NupMAT, indicating that opportunities to enhance yield through improving NUtE would only be possible at greater-than-average yield and N uptake levels. By measuring the effects of other reported variables on the residuals of the relationship between NUtE and N uptake, we observed that the variability in NUtE at particular levels of N uptake was greater for fall- than for winter-sown wheat, but it was similar for all wheat classes. The negative correlation between grain protein concentration and the residuals indicated a challenge to increase yield through improving NUtE with no penalties in grain protein. We conducted two field research experiments at difference sites during the 2015-16 and 2016-17 growing seasons in Kansas. In our experiment 1, we conducted on-farm experiments across three locations and two growing seasons in Kansas using 21 modern winter wheat genotypes grown under either standard (SM) or intensified management (IM) systems. Results showed that across all sites-years and genotypes, the IM increased yield by 0.9 Mg ha⁻¹ relative to the SM. Even in the lowest yielding background condition, the IM outyielded SM, and expectedly, the yield response to IM increased with the achievable yield of the environment. The yield response of genotypes to IM was related to the responses of biomass between the two management systems rather than harvest index, strongly driven by improvements in grain number while independent of changes in grain weight, and related to improvements in N uptake. In our experiment 2, we evaluated the partial contribution of 14 management practices on grain yield and the accumulation of N, P, K and S during the growing season using a single bread-wheat genotype grown under four site-years. Fungicide was the main treatment affecting yield and nutrient uptake. Overall, all nutrients were accumulated at a similar proportion at each growth stage relative to their respective accumulation at the end of the season. Shoot concentration for IM seemed to maintain higher concentration of nutrients as compared to the SM control during the growing season. This was emphasized by the significant increase in nutrition indices for N and S from SM to IM control, indicating possible luxury uptake under IM. Hence, crop intensification strategies may alter nutrient uptake at the end of season, but will not affect timing and rate of uptake during the growing season.
Keywords: Nitrogen economy; N utilization; Yield gap; N use efficiency; Macronutrients uptake